2013
DOI: 10.2967/jnumed.113.120089
|View full text |Cite
|
Sign up to set email alerts
|

The Use of O-(2-18F-Fluoroethyl)-l-Tyrosine PET for Treatment Management of Bevacizumab and Irinotecan in Patients with Recurrent High-Grade Glioma: A Cost-Effectiveness Analysis

Abstract: To date, the use of structural MR imaging (including contrast-enhanced and T2-weighted or fluid-attenuated inversion recovery-weighted images) is the standard method to diagnose tumor progression and to assess antiangiogenic treatment effects. However, several studies have suggested that O-(2-18 F-fluoroethyl)-L-tyrosine ( 18 F-FET) PET adds valuable clinical information to the information derived from structural MR imaging alone. We evaluated the effectiveness and cost-effectiveness of the addition of 18 F-FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…Several clinical studies have documented the diagnostic performance of 18 F-FET PET in primary brain tumors, and in conjugation with MRI, 18 F-FET PET has revealed supplementary information on tumor growth and metabolism [6], [34]. Furthermore, a good correlation between 18 F-FET uptake and treatment response has also been demonstrated in clinical studies [5][7], [35]. In the present study, we used a patient derived GBM cell line in a murine model and demonstrated the feasibility of monitoring a treatment response with 18 F-FET PET.…”
Section: Discussionmentioning
confidence: 95%
“…Several clinical studies have documented the diagnostic performance of 18 F-FET PET in primary brain tumors, and in conjugation with MRI, 18 F-FET PET has revealed supplementary information on tumor growth and metabolism [6], [34]. Furthermore, a good correlation between 18 F-FET uptake and treatment response has also been demonstrated in clinical studies [5][7], [35]. In the present study, we used a patient derived GBM cell line in a murine model and demonstrated the feasibility of monitoring a treatment response with 18 F-FET PET.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the necessary PET infrastructure is widely available, and the production of radiolabeled amino acids is well established with comparable costs to FDG. Any additional costs of this diagnostic technique can be potentially saved by the incurred costs of less reliable diagnostic imaging techniques [27].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the cost effectiveness of FET PET for therapy monitoring of antiangiogenic therapy has been analyzed (Heinzel et al, 2013). The data suggest that the additional use of FET PET in the management of these patients have the potential to avoid overtreatment and corresponding costs, as well as unnecessary patient side effects.…”
Section: Systemic Treatment Optionsmentioning
confidence: 99%